EXTENSIVE IMPACT MELTING ON THE H-CHONDRITE PARENT ASTEROID DURING THE CATACLYSMIC BOMBARDMENT OF THE EARLY SOLAR SYSTEM: EVIDENCE FROM THE ACHONDRITIC METEORITE DAR AL GANI 896 - Folco L.; Bland P.A.; D’Orazio M.; Franchi I.A.; Kelley S.P.; Rocchi S. (My University, 2004)
DaG 896 is an olivine-rich microporphyritic rock of komatiitic composition. Both the olivine composition (Fa17.5±2.1, [Mn/Mg] = 0.0061) and the bulk oxygen isotopic composition (δ O = +2.55, δ O = +3.50) indicate that DaG 896 is a sample of the H-chondrite parent body. The bulk chemistry shows an H-chondritic distribution of lithophile elements, whereas chalcophile and siderophile elements are strongly depleted, indicating formation through whole-rock melting (or nearly so) of H-chondrite material, nearly complete loss of the metal plus sulfide component, and crystallization without significant igneous fractionation. Superheated, severely shocked chondritic relics (∼10 vol%), typically in the form of corroded lithic fragments <100 μm in size intimately distributed within the igneous lithology, indicate that melting was triggered by a highly energetic impact, which possibly induced shock pressures of ∼80–100 GPa. The relatively young 3.704 ± 0.035 Ga Ar- Ar crystallization age is consistent with the impact melting origin, as magmatism in the asteroid belt was active only in the first hundred million years of solar system history.